MEMBANGUN LEGAL BASIS PENGISIAN JABATAN DALAM PENINGKATAN KUALITAS PELAYANAN PUBLIK - Retno Mawarini Sukmariningsih (Masalah-Masalah Hukum, 2015)
Civil servants management at the Regional Agencies implemented by local governments in accordance with the legislation., The substance of the requirements for filling the positions (Contract Position Determination and Structural), can be set at the level of local regulations. A Civil State Apparatus in addition to unifying the nation primarily as a public servant and qualified professionals. In building the legal basis of structural filling positions, especially at the local level through the establishment of regional regulation is not easy, a fact often creates debate table because political aspects are the dominant rather than normative aspects required in forming the Government Area and the persistence of attitudes like and dislike.